Deep Phenotyping of CD11c+ B Cells in Systemic Autoimmunity and Controls - Rincon-Arevalo, Hector; Wiedemann, Annika; Stefanski, Ana-Luisa; Lettau, Marie; Szelinski, Franziska; Fuchs, Sebastian; Frei, Andreas Philipp; Steinberg, Malte; Kam-Thong, Tony; Hatje, Klas; Keller, Baerbel; Warnatz, Klaus; et al. (Frontiers in Immunology, 2021)
Circulating CD11c+ B cells are a key phenomenon in certain types of autoimmunity and have also been described in the context of regular immune responses (i.e. infections, vaccination). Using mass cytometry to profile 46 different markers on individual immune cells, we systematically confirmed the presence of increased CD11c+ B cells in the blood of systemic lupus erythematosus (SLE) patients. Significant differences in the expression of CD21, CD27 and CD38 were observed between CD11c- and CD11c+ B cells, with a direct correlation of the frequency of CD11c+ and CD21-CD27- B cells, as well as CD21-CD38- B cells, which was most pronounced in SLE compared to primary Sjögren’s syndrome patients (pSS) and healthy donors (HD). CD11c+ B cells were mainly found among memory subsets, and enriched in CD27-IgD-, CD21-CD27- and CD21-CD38- B cell phenotypes. CD11c+ B cells from all donor groups (SLE, pSS and HD) showed enhanced CD69, Ki-67, CD45RO, CD45RA and CD19 expression, and reduced CXCR5 and CD21 expression. Those of SLE patients showed a particular profile of enhanced expression of the checkpoint molecules CD86, PD1, PDL1, CD137, VISTA and CTLA-4 compared to HD. The substantial egress of CD11c+ B cells with a CD21- phenotype into the blood, expressing distinct activation and checkpoint markers, points to intensive extrafollicular B cell activation and abnormal immune regulation in the chronic phase of the disease.